Características de dossel e produção de milho submetido a arranjos espaciais de planta e adubação nitrogenada em plantio direto - Coutinho Neto, André Mendes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Nitrogen fertilization and the spatial arrangement of plants are among the most important management practices to achieve greater productivity of corn. The objective of this work was to evaluate, in two no-tillage areas, with different crop sequences (corn/corn and leguminous/corn) the influence of nitrogen fertilization and spatial arrangement in leaf area index (LAI), in photosynthetically active radiation (PAR), the nitrogen in biomass and productivity of corn, with emphasis on yield components. The experiments were conducted in Jaboticabal, SP, Brazil, during two seasons, in a clayey Oxisol under no-tillage since 1990. The experimental design was a randomized block, according to a factorial arrangement 3 x 2 x 2 [three nitrogen rates (0, 80, and 180 kg ha -1); two row spacing (0.80 and 0.45 m) and two plant densities (55 and 90 thousand plants ha-1)]. The following variables were evaluated: plant height and height of insertion of the first ear, stalk diameter, number of kernel rows per ear, number of kernels per ear, thousand grain weight, prolificacy (number of ears per plant), leaf area index (LAI), photosynthetically active radiation (PAR), N biomass and grain yield. Regardless of the N rate and plant density, row spacing of 0.45 m provided greater productivity, heavier grains, greater PAR and number of kernels and ears per plant. Stalk diameter, number of kernels, thousand grain weight and prolificacy decreased with increasing plant density, while plant height, ear insertion height, LAI and PAR increased with plant density. The yield depended on the plants density considered, and the higher yields obtained with the population of 90,000 plants in the presence of the highest N rate. The grain yield was positively related with yield components: number of rows per ear, number of grains per ear, thousand grain weight, LAI, N biomass and PAR

A adubação nitrogenada e o arranjo espacial de plantas estão entre as práticas de manejo mais importantes para a obtenção de maior produtividade de milho. O objetivo do trabalho foi avaliar, em duas áreas de plantio direto, com distintas sucessões de culturas (milho/milho e leguminosa/milho), a influência da adubação nitrogenada e do arranjo espacial no índice de área foliar (IAF), na radiação fotossinteticamente ativa interceptada (RFAint), no nitrogênio na biomassa, nos componentes do rendimento e na produtividade de grãos de milho (cultura de verão). Os experimentos foram conduzidos durante dois anos agrícolas, em Latossolo Vermelho eutroférrico argiloso, em sistema plantio direto desde 1990. O delineamento experimental utilizado foi em blocos casualizados, em arranjo fatorial 3 x 2 x 2 [três doses de N (0, 80 e 180 kg ha-1); dois espaçamentos entrelinhas (0,80 e 0,45 m) e duas populações de plantas (55 e 90 mil plantas por ha)]. Foram avaliadas as variáveis: altura de planta, altura de inserção da primeira espiga, diâmetro de colmo, número de fileiras de grãos por espiga, número de grãos por espiga, massa de mil grãos, prolificidade (número de espigas por planta), IAF, RFAint., N na biomassa e produtividade de grãos. Independentemente da dose de N e da população de plantas, o espaçamento entrelinhas de 0,45 m proporcionou maior produtividade, grãos mais pesados, maior RFA e número de grãos e de espigas por planta. Diâmetro do colmo, número de grãos por espiga, massa de mil grãos, prolificidade diminuíram com o aumento da densidade de plantas, ao passo que a altura de planta, altura de inserção de espiga, IAF e RFAint. aumentaram com o adensamento de plantas. A produtividade de grãos dependeu da densidade plantas, sendo os maiores rendimentos obtidos com a população de 90 mil plantas/ha na presença da maior dose de N. A produtividade de grãos relacionou-se positivamente com o número...
Keywords: Milho; Adubação; Nitrogenio na agricultura; Fertilizantes nitrogenados; Produtividade agrícola; Nitrogen in agriculture